Effect of Poly(ADP-ribose) Polymerase Inhibition on the Injury of Intestinal Mucosal Barrier in Rat Model with Severe Acute Pancreatitis - Xinting Pan; Yunpeng Zhu; Yan Liu; Tianjiao Lin; Ainqin Li; Qingyun Zhu (American Journal of Internal Medicine, 2026)
Background: The injury of intestinal mucosal barrier in the later period of severe acute pancreatitis (SAP) results in flora migration with the endotoxin and bacterium entering blood circulation, final result of bacteremia, multiple organ dysfunction syndrome (MODS), eventually death. poly (ADP-ribose) polymerase-1(PARP-1) is a nuclear DNA-binding protein that has been revealed a wide role in DNA repair, chromatin structure, necrosis, inflammation and immune function. We plan to determine whether PARP-1 and its inhibition affect the injury of intestinal mucosal barrier in SAP. Methods: SAP was induced by 6 hourly intraperitoneal injection of cerulein (50ug/kg), with lipopolysaccharide (10mg/kg) in the last time. At 30 min prior, rats were treated with the PARP inhibition 3-Aminobenzamide (3-AB) or normal saline. 40 rats were randomly separated into 4 groups of a normal control group, a SAP group, a SAP with inhibition group and an inhibition group. After 12 hours, all rats were killed. We compared serum amylase, interleukin-6 (IL-6), celiac morphological changes, pancreatic pathological injury, intestinal histology. Activities of PARP-1, nuclear factor-kappa B (NF-kB), Occludin in the intestine were also examined. Result: The inflammation and injury has been showed seriously in the intestines. with SAP, the expression of PARP-1 and NF-kB also has been shown high level. But with administration of PARP inhibitor, 3-AB, the severity of SAP and pancreatitis-associated intestinal injury was significantly attenuated, the protein expression of PARP-1 and NF-kB was significantly decreased. Conclusion: Our findings indicate that PARP inhibitors played a positive role in the injury of intestinal mucosal barrier in rat model with SAP.